Causal relationship in classroom research skills among teachers in the deep South of Thailand - Lateh, Afifi; Ruengrung, Sathaphorn; Liwan, Attapon (Edelweiss Applied Science and Technology, 2025)
Developing classroom research skills requires knowledge, ability, and practice. Understanding the factors that influence these skills is important. This study aimed to investigate the causal relationship among classroom research skills of teachers in the Deep South of Thailand. The sample included 239 teachers from three southern border areas who completed an online questionnaire comprising four parts: general information, self-assessment of classroom research skills, true-false questions to evaluate classroom research knowledge, and a 5-point Likert scale assessing factors influencing classroom research skills, including curriculum and training quality, attitude, motivation, administrative support, and the impact of workload and unrest. The structural equation model hypothesis was tested using PLS-SEM, and results showed that six hypotheses were statistically significant. Curriculum and training quality, as well as academic standing, had a positive influence on classroom research skills. Curriculum and training quality had a positive influence on attitude and knowledge. Administrative support had a positive influence on motivation, while the impact of workload and unrest had a negative effect. These results reflect the importance of quality curriculum and training to build teachers’ confidence in conducting research systematically. Although the study found that the impact of workload and unrest did not have a direct effect on classroom research skills, it is possible that teachers in the area were already familiar with the challenges they face and able to perform their duties, including conducting research, while managing these challenges.